2019
DOI: 10.1177/0961000619880937
|View full text |Cite
|
Sign up to set email alerts
|

The use of mobile devices and applications for health information: A survey of Croatian students

Abstract: This study aims to understand the information behaviours of youth seeking health information on mobile devices and to explore differences by prior knowledge, gender and grade level. A survey was conducted in two high schools in Osijek, Croatia. Results indicate that among the total 408 participants, 84.3% reported having used mobile devices for health information and 54.7% reported having used applications for health information. Students seek health information about physical activity and eating issues/nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…A study conducted by Kim, Martinovic and Katavic (2019) found that attendance has small value, but significant effects on student learning and performance. Students who skipped class on a given date were significantly more likely to respond incorrectly to questions relating to material covered that day than students who were present.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Kim, Martinovic and Katavic (2019) found that attendance has small value, but significant effects on student learning and performance. Students who skipped class on a given date were significantly more likely to respond incorrectly to questions relating to material covered that day than students who were present.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results on use of se-atlas show that the system is mainly used via laptop or desktop computers and only a smaller proportion of the study participants indicated mobile use (18.17 %), especially the group of members of patient organisations. However, this result is not in line with the increasing trend of mobile device use on the internet and does not decrease the relevance of mobile use [27][28][29].…”
Section: Background and Purposementioning
confidence: 87%
“…Despite the importance, little progress has been made to meet the need of providing online health information. Research on young people's online health mostly rely on data collected from questionnaire surveys or interviews, with the number of data samples being fewer than 1000 [11][12][13]. These can hardly be expected to represent the actual information needs of young people.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding data analysis methods are also different. For the questionnaires and survey data, descriptive statistical analysis, correlation analysis, and multiple logistic regression analysis are generally applied [ 11 , 12 , 14 ]. For interview data, many studies use content analysis and statistical analysis [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%